Leukoerythroblastosis as an Unusual Presentation of Parvovirus B19 Infection in a Sickle Cell Patient - Pratik A. Patel; Elizabeth P. Weinzierl; Daniel S. Wechsler (Case Reports in Pediatrics)
Parvovirus B19 infection in pediatrics most commonly causes fifth disease, a mild viral illness. Hematologic manifestations include severe anemia, especially in patients with chronic hemolytic anemias or who are immunocompromised. Because of the shortened life span of erythrocytes in patients with sickle cell disease, parvovirus infection can cause transient aplastic crisis which can be life-threatening. However, leukocytosis and thrombocytosis are rarely seen. We report leukoerythroblastosis as an unusual presentation of acute parvovirus B19 infection in a previously splenectomized 12-year-old boy with sickle cell disease.